2004
DOI: 10.1007/s00249-004-0438-8
|View full text |Cite
|
Sign up to set email alerts
|

Soft perforation of planar bilayer lipid membranes of dipalmitoylphosphatidylcholine at the temperature of the phase transition from the liquid crystalline to the gel state

Abstract: In contrast to the widely used method of electroporation, the method of soft perforation of lipid bilayers is proposed. It is based on the structural rearrangement of the lipid bilayer formed from disaturated phospholipids at the temperature of the phase transition from the liquid crystalline state to the gel state. This allows us to obtain a lipid pore population without the use of a strong electric field. It is shown that the planar lipid bilayer membrane (pBLM) formed from dipalmitoylphosphatidylcholine in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 19 publications
5
72
0
Order By: Relevance
“…However, Antonov et al [39] reported the selectivity order of monovalent cations for soft perforation pores generated at the BLM’s phase transition temperature. They suggested that the hydration force is responsible for cation selectivity of planar BLM at soft perforation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Antonov et al [39] reported the selectivity order of monovalent cations for soft perforation pores generated at the BLM’s phase transition temperature. They suggested that the hydration force is responsible for cation selectivity of planar BLM at soft perforation.…”
Section: Discussionmentioning
confidence: 99%
“…This variety is to be expected, given the fluidity of BLM and the possibility of multiple modes of interaction between PNP and BLM, including PNP aggregation at, or in, BLM to form an ion-transporting complex [40]. Alternatively, PNP could cause a phase transition in BLM at the point of contact [41], which could trigger pore formation due to structural rearrangement from the liquid crystalline state to the gel state [39]. …”
Section: Discussionmentioning
confidence: 99%
“…They exhibit quantized currents corresponding to large pores with a narrow distribution of sizes (Antonov et al. 1980, 2005; Boheim et al. 1980) and moderate ion selectivity (Antonov et al.…”
Section: Intrinsic Leakage Of Membranesmentioning
confidence: 99%
“…1980) and moderate ion selectivity (Antonov et al. 2005). The presence of lysolipids at the gel-to-liquid phase transition dramatically enhances membrane leakage, and this is proposed to occur through lysolipid-stabilized pores in the boundary of the partially melted solid phase (Mills and Needham 2005).…”
Section: Intrinsic Leakage Of Membranesmentioning
confidence: 99%
“…This finding was first reported by Yafuso and collaborators (2) on oxidized cholesterol membranes. Numerous subsequent reports show that one finds channel-like events in synthetic lipid membranes in the complete absence of proteins (3)(4)(5)(6)(7)(8)(9)(10). The channels reported in those studies are typically of similar conductance (several 10 to 100 pS) and lifetime (a few ms to several 100 ms) than those of protein channels.…”
Section: Introductionmentioning
confidence: 96%